Pengaruh Disiplin Kerja dan Pengalaman Kerja Terhadap Kinerja Karyawan Daiwani Bordir Tasikmalaya - Muhammad Azham Abusalam; Arga Sutrisna; Ai Kusmiyati Asyiah (Jurnal Manajemen Riset Inovasi, 2024)
This research was conducted with the aim of determining the influence of work discipline and work experience on the performance of Daiwani Embroidery Tasikmalaya employees. The method used in this research is a survey method using data obtained directly through questionnaires distributed to 60 respondents who are employees of Daiwani Embroidery Tasikmalaya. The technique used in this research is multiple regression analysis. Based on the research results, it is known that work discipline and work experience simultaneously have a significant effect on the performance of Daiwani Embroidery Tasikmalaya employees. Work Discipline partially has a significant effect on the Performance of Daiwani Embroidery Tasikmalaya Employees. Work experience partially has a significant effect on the performance of Daiwani Embroidery Tasikmalaya employees.